Platelet transfusion: a systematic review of the clinical evidence. Issue 5 (12th November 2014) - Kumar, Ambuj; Mhaskar, Rahul; Grossman, Brenda J.; Kaufman, Richard M.; Tobian, Aaron A.R.; Kleinman, Steven; Gernsheimer, Terry; Tinmouth, Alan T.; Djulbegovic, Benjamin; AABB Platelet Transfusion Guidelines Panel
<x xml:space="preserve">Abstract</x> Background Platelet (PLT) transfusion is indicated either prophylactically or therapeutically to reduce the risk of bleeding or to control active bleeding. Significant uncertainty exists regarding the appropriate use of PLT transfusion and the optimal threshold for transfusion in various settings. We formulated 12 key questions to assess the role of PLT transfusion. Study Design and Methods We performed a systematic review (SR) of randomized controlled trials (RCTs) and observational studies. A comprehensive search of PubMed, Web of Science, and Cochrane registry of controlled trials was performed. Methodologic quality of included studies was assessed and a meta‐analysis was performed if more than two studies with similar designs were identified for a specific question. Results Seventeen RCTs and 55 observational studies were included in the final SR. Results from RCTs showed a beneficial effect of prophylactic compared with therapeutic transfusion for the prevention of significant bleeding in patients with hematologic disorders undergoing chemotherapy or stem cell transplantation. We found no difference in significant bleeding events related to the PLT count threshold for transfusion or the dose of PLTs transfused. Overall methodologic quality of RCTs was moderate. Results from observational studies showed no evidence that PLT transfusion prevented significant bleeding in patients undergoing central venous catheter insertions, lumbar puncture, or other surgical procedures. The methodologic quality of observational studies was very low. Conclusion We provide a comprehensive assessment of evidence on the use of PLT transfusions in a variety of clinical settings. Our report summarizes current knowledge and identifies gaps to be addressed in future research.